PENGARUH PERTUMBUHAN ASET, PERTUMBUHAN PENJUALAN, PROFITABILITAS DAN PAJAK TERHADAP SUMBER PENDANAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2013-2014 - Heni Yusnita; Yessi Mutia Basri; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study was conducted to determine the effect of the partial Funding Source on the Growth Assets, Sales Growth, Profitability and Tax on Manufacturing Companies Listed on the Stock Exchange. The study period of 2013-2014.The population of as many as 156 companies.Selection of the sample using Non Probability Sampling Techniques with purposive sampling method in order to obtain a sample of 88 companies. Fundingdecisions are represented LLT, Growth Assets represented by ASG, Penjuala Growth, Profitability ROE, and taxes as independent variables and the dependent variable is theSource of Funding. Data processing was performed with SPSS for Windows Evaluation Version 21:00. The regression results obtained demonstrate the value of F (4.685) greater than F table (1.984), meaning that Asset Growth, Sales Growth, Profitability, and Taxation jointly significant effect on the Funding Source. While partially Asset Growth variables affect the sources of funding where t count (3.282) is greater than t table (1.984). Sales Growth variables affect the sources of funding where t count (3.124) is greater than t table (1.984). Profitability variables which affect the Funding Source tcount (2.924) is greater than t table (1.984). Taxes and variables which affect the Funding Source t count (2.452) is greater than t table (1.984). Correlation coefficient (R) of 0.725 or 72.5% indicates that there is a strong relationship between Growth Assets, Sales Growth, Profitability and Taxes on Funding Sources. The coefficient of determination (Adj R2) of 0.482 indicates that amounted to 48.2% of the Funding Source affected by Asset Growth, Sales Growth, Profitability and Tax, while 51.8% are influenced by other factors not examined.Keywords: Sources of Financing, Asset Growth, Sales Growth, Profitability and Taxes